That darkness - Black, Lisa, 1963- (Black, Lisa, 1963- Gardiner and Renner thriller., 2016)
Cleveland Police Department forensic investigator Maggie Gardiner investigates a female teenagedvictim that no one has reported missing, and a killer with a unique sense of justice.